Utilization of Fertilizers for Improving The Process Rate of Organic Material Degradation in Anaerobic Reactor - Adelia Anju Asmara; Agoes Soegianto; Trisnadi Widyaleksono Catur Putranto; Hairul Amin; Nur Indradewi Oktavitri (IPTEK Journal of Proceedings Series, 2014)
This study aimed to assess utilization of fertilizers as nutrient in the anaerobic reactor. Nutrient is one important characteristic of waste for the treatment. Nutrient is required for the growth and reproduction process of microorganisms which involved in the anaerobic process. The wastewater used in this research is tofu wastewater. Gandasil B fertilizer has N 6 mg/l and P 20 mg/l. While for Gandasil D fertilizer has N 20 mg/l and P 15mg/l. Anaerobic reactor has 1000 ml of capacity which contain 600 ml of wastewater, 100 ml of liquid fertilizer, and 300 ml of space blank. Anerobic reactor observed for 14 days with 5 observed parameters. Those parameters are TSS, VSS, COD, N, and P. After 14 days, added of Gandasil B fertilizer decreased the concentration of TSS, VSS, COD, N, and P amounted to 57,56%, 26,84%, 80,08%, 96,75%, and 93,18%. compared to the 0th day. While the addition of Gandasil D fertilizer decreased the parameters amounted to 3,48%, 6,21%, 86,72%, 58,10%, and 90,78%. In conclusion, Gandasil B fertilizer in the anaerobic reactor improves the rate of organic material degradation more effectively than Gandasil D fertilizer.Keywords - Anaerobic reactor, COD, fertilizer, N, nutrient, P, TSS, VSS